2020
DOI: 10.1155/2020/3218350
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Induced Calcium Pyrophosphate Deposition Disease of the Lumbar Spine

Abstract: Inflammatory arthritis, such as pseudogout or otherwise referred to as calcium pyrophosphate (CPP) crystal arthritis or calcium pyrophosphate deposition (CPPD) disease, is characterized by the deposition of crystal formation and deposition in large joints. CPPD is known to affect the elderly population and commonly manifests as inflammation of knees, hips, and shoulders. CPPD disease involving the spine has been infrequently encountered in practice and rarely described in the literature. Here, we describe a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 16 publications
0
22
0
2
Order By: Relevance
“…However, it is unclear what role these previous surgeries had in the development of CPPD. Although local trauma is a known risk factor for CPPD [39][40][41][42], our patient presented eight years after his previous spine surgeries. Ogawa et al reported the first case of acute lumbar spinal pseudogout occurring four weeks after spinal instrumentation [39] .…”
Section: Discussionmentioning
confidence: 87%
“…However, it is unclear what role these previous surgeries had in the development of CPPD. Although local trauma is a known risk factor for CPPD [39][40][41][42], our patient presented eight years after his previous spine surgeries. Ogawa et al reported the first case of acute lumbar spinal pseudogout occurring four weeks after spinal instrumentation [39] .…”
Section: Discussionmentioning
confidence: 87%
“…В работе I. Greca и соавт. [20] описан случай прогрессирующей боли в спине, возникшей у 80-летней женщины через год после травмы позвоночника при падении с лестницы, с последующим развитием острого дисцита, связанного с отложениями кристаллов ПФК (диагноз БДПК был подтвержден данными биопсии). При этом иных локализаций ХК у пациентки не выявлено, сывороточные уровни СРБ и СОЭ были в пределах нормы, а содержание парагормона, щелочной фосфатазы, магния не определяли.…”
Section: при осмотре выявлялись резкая болезненность и припухлость при пальпации коленных суставов ограничение сгибания в них ввиду выражunclassified
“…Arthritiden sind durch intrasynoviale Kristall-Depositionen von zumeist metabolischen Produkten verursacht und sind mit einer floriden oder aber auch chronischen Entzündung assoziiert. Die wichtigsten histopathologisch dia- gnostizierbaren Kristallarthropathien umfassen: Die Gicht, die Chondrocalcinose, die Kalzinose-Arthropathien und die Oxalose [4]. Bei der letzteren Erkrankung handelt es sich um eine Erkrankung, welche in erster Linie im Nierenparenchym sowie im Knochengewebe und selten im Bereich der Gelenke lokalisiert ist.…”
Section: Kristallinduzierte Arthritidenunclassified